Memahami teks Bacaan Dengan Metode Cooperative Integrated Reading And Composition (CIRC) Pemahaman Teks Siswa Sekolah Dasar - Fitriami, Fadilla; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study is to describe the effect of using the Cooperative Integrated Reading and Composition (CIRC) method to the text understanding of Grade V students of the Elementary School Group I, Akabiluru District, Lima Puluh Kota. This type of research is Quasy Experiment (quasi-experimental) with pretest-posttest non-equivalent group design. The sample uses purposive sampling with lottery. Samples totaled 37 people. The results of the t-test are greater than the t-table. Which is t-count of 2.2169 and t-table 2.0301 with a significance level of α = 0.05. By getting t-count greater than t-table means Ho is rejected and Ha is accepted. It was concluded that there was an influence of the CIRC method on the understanding of the text of Grade V students of the Elementary School in Cluster I of Akabiluru District, Lima Puluh Kota.